2013
DOI: 10.1111/iwj.12063
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of topical royal jelly on healing of diabetic foot ulcers: a double‐blind placebo‐controlled clinical trial

Abstract: Foot ulcers are major sources of morbidity in individuals with diabetes mellitus. As royal jelly (RJ, a worker honey bee product) contains enzymatic, antibacterial and vasodilative properties, it can potentially help in healing of diabetic foot ulcers (DFUs). This study aimed to evaluate the efficacy of topical RJ on healing of DFUs. Diabetic patients with foot ulcers who were referred to us at Khorshid Hospital, Isfahan, Iran, were managed by offloading, infection control, vascular improvement and debridement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(55 citation statements)
references
References 33 publications
(36 reference statements)
1
47
0
2
Order By: Relevance
“…Various studies have reported antimicrobial activities of royal jelly against bacteria, fungi, and viruses, while in animal models, hypotensive, antitumour, antihypercholesterolemic, and anti-inflammatory activities have been observed (Ramadan and Al-Ghamdi, 2012). Moreover, antidiabetic properties, positive effects on benign prostatic hyperplasia, and wound healing of diabetic foot ulcers have been verified in clinical trials (Siavash et al, 2015; Khoshpey et al, 2016). Most studies concern crude royal jelly or protein and lipid subfractions, but in several cases the activity of singular compounds has been ascertained.…”
Section: Royal Jellymentioning
confidence: 96%
“…Various studies have reported antimicrobial activities of royal jelly against bacteria, fungi, and viruses, while in animal models, hypotensive, antitumour, antihypercholesterolemic, and anti-inflammatory activities have been observed (Ramadan and Al-Ghamdi, 2012). Moreover, antidiabetic properties, positive effects on benign prostatic hyperplasia, and wound healing of diabetic foot ulcers have been verified in clinical trials (Siavash et al, 2015; Khoshpey et al, 2016). Most studies concern crude royal jelly or protein and lipid subfractions, but in several cases the activity of singular compounds has been ascertained.…”
Section: Royal Jellymentioning
confidence: 96%
“…This is due to its vasodilation effects around the affected wound, which can help to dilate the blood vessels to enhance blood flow. It also helps to prevents infections due to its antimicrobial activities [115]. …”
Section: Health Benefits Of Royal Jellymentioning
confidence: 99%
“…However, observational studies and case reports would have been of value if they had reported safety data although there are reports about amputation. Honey's superiority as reported by these case reports and observational studies based on amputation rate can be justified if the [17,19] used topical royal jelly and its composition was water (50e60%), protients (18%), carbohydrates (15%), lipids (3e6%), mineral salts (1.5%), vitamins, 10-hydroxyl-2-decenoic acid, insulin like peptide. Manuka honey was used by Kamaratos A V et al in a randomized clinical trial [14].…”
Section: Discussionmentioning
confidence: 96%